Void content, tensile, vibration and acoustic properties of kenaf/bamboo fiber reinforced epoxy hybrid composites - Ismail, Ahmad Safwan; Jawaid, Mohammad; Naveen, Jesuarockiam (MDPI, 2019)
This study aims to investigate the void content, tensile, vibration and acoustic properties of kenaf/bamboo fiber reinforced epoxy hybrid composites. The composites were made using the hand lay-up method. The weight ratios of kenaf/bamboo were 30:70, 50:50 and 70:30. Further, kenaf and bamboo composites were fabricated for the purpose of comparison. The hybridization of woven kenaf/bamboo reduced the void content. The void contents of hybrid composites were almost similar. An enhancement in elongation at break, tensile strength and modulus of hybrid composites was observed until a kenaf/bamboo ratio of 50:50. Kenaf/bamboo (50:50) hybrid composite displays the highest elongation at break, tensile strength and modulus compared to the other hybrid composites which are 2.42 mm, 55.18 MPa and 5.15 GPa, respectively. On the other hand, the highest natural frequency and damping factors were observed for Bamboo/Kenaf (30:70) hybrid composites. The sound absorption coefficient of composites were measured in two conditions: without air gap and with air gap (10, 20, 30 mm). The sound absorption coefficient for testing without air gap was less than 0.5. Introducing an air gap improved the sound absorption coefficient of all composites. Hence, hybrid kenaf/bamboo composites exhibited less void content, as well as improved tensile, vibration and acoustic properties.